مالية البلدية بين التبعية و الاستقلال - سعودي علي- سليماني سامي (جامعة المسيلة, 2022)
هذه الدراسة التي تحمل اسم المالية البلدية بين الاستقلالية و التبعية ، تناولت موضوع مظاهر الاستقلالية المالية البلدية من حيث التعريف و الخصائص وكذلك من حيث موارده المالية التي تحتاجها لتغطية الوظائف المتعددة وميزانيتها من مراحل إعدادها إلى كيفية تنفيذها ، ومظاهر التبعية المالية للبلدية من حيث مختلف أنواع الرقابة التي تمارسها الهيئات الرقابية على المالية البلدية و كذلك الإعانات الحكومية التي تجعلها تابعة للسلطة المركزية ، لتختتم بمجموعة من النتائج وإعطاء التوصيات من خلالها . Study summary: This study, which bears the name of Municipal Finance between Independence and Dependency, dealt with the issue of manifestations of municipal financial independence in terms of definition and characteristics, as well as in terms of its financial resources that it needs to cover multiple functions and its budget from the stages of preparation to how to implement it, and manifestations of financial dependency of the municipality in terms of various types of control Which are exercised by the supervisory bodies on municipal finance, as well as government subsidies that make them subordinate to the central authority, to conclude with a set of results and give recommendations through them.
Keywords: التبعية- الاستقلالية -البلدية